2012
DOI: 10.2310/8000.2011.110316
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic bacterial meningitis: an unmasked threat

Abstract: Iatrogenic bacterial meningitis (IBM) is a rare but serious complication of neuraxial procedures, such as spinal and epidural anesthesia or lumbar puncture. We report a case of a 46-year-old female who presented to the emergency department with bacterial meningitis after spinal anesthesia. We review the existing literature outlining the pathogenesis, vector hypothesis, diagnosis, treatment, and prevention as they relate to IBM. We highlight the role of the emergency physician in the rapid diagnosis of this dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
1
0
2
Order By: Relevance
“…Patients undergoing neuraxial anesthesia are at risk for infections that can lead to complications such as arachnoiditis, epidural abscess, meningitis, sepsis, cardiac arrest, or death 1‐7 . Infectious complications are known to cause serious and devastating morbidity and mortality; however, until recently, anesthesia professionals believed these complications to be rare in patients receiving neuraxial anesthesia 1‐7 . In the past 10 years, new studies have shown a higher incidence of infectious complications associated with neuraxial anesthesia than were previously reported 8,9 …”
Section: Population Intervention Comparison Outcome (Pico) Frameworkmentioning
confidence: 99%
“…Patients undergoing neuraxial anesthesia are at risk for infections that can lead to complications such as arachnoiditis, epidural abscess, meningitis, sepsis, cardiac arrest, or death 1‐7 . Infectious complications are known to cause serious and devastating morbidity and mortality; however, until recently, anesthesia professionals believed these complications to be rare in patients receiving neuraxial anesthesia 1‐7 . In the past 10 years, new studies have shown a higher incidence of infectious complications associated with neuraxial anesthesia than were previously reported 8,9 …”
Section: Population Intervention Comparison Outcome (Pico) Frameworkmentioning
confidence: 99%
“…in Pseudomonas spp. ; med njimi so najpogosteje dokazani zeleneči streptokoki (1,3). Streptococcus salivarius je pomemben povzročitelj iatrogenega meningitisa (4).…”
Section: Uvodunclassified
“…Meningitis je redek zaplet in je mikrobiološko potrjen le v 0,3-5 % primerov (6). Med zelenečimi streptokoki je najpogostejši povzročitelj iatrogenega meningitisa S. salivarius (3). Lahko povzroča še infekcijski endokarditis, sepso in bakteriemijo pri imunsko oslabelih bolnikih (8).…”
Section: Razpravljanjeunclassified